Risk factors for injury in early childhood: First findings from Wave 1 of Growing Up in Australia, the Longitudinal Study of Australian Children - Blakemore, T (My University, 2005)
Injury is noted as the leading cause of child death and child ill health in Australia. It is therefore imperative for the formation of effective prevention policy and practice parameters that the nature, scope and associated risk factors for childhood injury are well understood. Data from Wave 1 of Growing Up in Australia, the Longitudinal Study of Australian Children (Growing Up in Australia), is utilised in this paper to present a unique and representative overview of the spectrum and extent of physical injuries experienced by Australian children in early childhood. An assessment of risk factors associated with such injuries is also presented. The research is informed by ecological theory and conceptualises potential risk factors for early childhood injury as including various characteristics of the child and their family and their interaction with society and the broader environment. As well as being an important policy issue in its own right - with broader policy links to education, health, and environmental modification; serious and/or frequent childhood injury has also been suggested as a significant marker or potential indicator of child maltreatment. This potential relationship will be explored further in an anticipated series of papers assessing risk and protective factors in the early childhood of Australian children.
Keywords: Health -- Injury; Health; Health and wellbeing; Health; Injury; Health and wellbeing